Association between Anxiety and Pain in Dental Treatment: A Systematic Review and Meta-analysis. (February 2017) - Lin, C.-S.; Wu, S.-Y.; Yi, C.-A.
Accumulating evidence has revealed that dental anxiety (DA), as a dispositional factor toward the dental situation, is associated with the state anxiety (SA) and pain related to dental procedures. However, conclusions from individual studies may be limited by the treatment procedures that patients received, the tools used to assess DA, or the treatment stages when anxiety or pain was assessed. It is unclear whether DA, at the study level, accounts for the variance in pretreatment SA. The impact of DA and SA on pain at different treatment stages has not been systematically investigated. To address these questions, we present novel meta-analytical evidence from 35 articles (encompassing 47 clinical groups) that investigated DA in a clinical group. Subgroup analyses revealed that the studies of surgical and nonsurgical procedures did not significantly differ in either DA or pretreatment SA. Furthermore, metaregressions revealed DA as a significant predictor that explained the variance in SA assessed before and during treatment but not after treatment. The findings suggest that patient DA has a significant impact on patient SA. Metaregressions revealed DA as a significant predictor that explained the variance in expected pain, pain during treatment and posttreatment pain. In contrast, pretreatment SA was a significant predictor that explained the variance in expected pain. The findings reveal that DA has a consistent impact on pain through the entire period of dental treatment. Altogether, the findings highlight the role of DA as an overall indicator for anxiety and pain, across different types of dental procedures or treatment stages. We conclude that anxiety should be assessed as a critical step not only in anxiety management for high-DA patients, but also in pain control for all dental patients.